2009
DOI: 10.1038/jp.2009.119
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of methicillin-susceptible and methicillin-resistant Staphylococcus aureus in a neonatal intensive care unit, 2000–2007

Abstract: Objective: To assess the epidemiology of methicillin-susceptible Staphylococcus aureus (MSSA) and methicillin-resistant S. aureus (MRSA) infections in a neonatal intensive care unit (NICU).Study Design: A retrospective chart review was conducted from 2000-2007; demographic and clinical characteristics of infected infants and crude mortality were assessed.Results: During the study period, there were 123 infections caused by MSSA and 49 infections caused by MRSA. Although the types of infections caused by MSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 18 publications
5
80
3
1
Order By: Relevance
“…The increasing prevalence of USA300 in pregnant women, coinciding with the increased incidence in the NICU and in newborn nurseries (6,18,35), suggests that MRSA may be vertically transmitted from mother to infant. We recently reported that infants admitted to the NICU who developed MRSA infections were younger at presentation than infants with MSSA infections (median age of 23 days versus 32 days, respectively; P ϭ 0.03), suggesting potential evidence of vertical transmission (7). Using a variety of methods in different populations, several authors have recently studied the risk of vertical transmission of MRSA, resulting in infant colonization, from mothers detected by prenatal anovaginal cultures (2) or by culture of the anterior nares and vagina during labor (19,28,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing prevalence of USA300 in pregnant women, coinciding with the increased incidence in the NICU and in newborn nurseries (6,18,35), suggests that MRSA may be vertically transmitted from mother to infant. We recently reported that infants admitted to the NICU who developed MRSA infections were younger at presentation than infants with MSSA infections (median age of 23 days versus 32 days, respectively; P ϭ 0.03), suggesting potential evidence of vertical transmission (7). Using a variety of methods in different populations, several authors have recently studied the risk of vertical transmission of MRSA, resulting in infant colonization, from mothers detected by prenatal anovaginal cultures (2) or by culture of the anterior nares and vagina during labor (19,28,30).…”
Section: Discussionmentioning
confidence: 99%
“…Vertical transmission from mothers to infants at delivery has also been proposed as a possible mechanism of acquisition of CA-MRSA (1,2,7,28). S. aureus has been reported to colonize the vagina in 4 to 22% of pregnant women (2,4,9,13,14).…”
mentioning
confidence: 99%
“…Reports of MRSA ophthalmic infections are numerous in the literature. They are more commonly seen in patients in neonatal ICUs [61][62][63], in post-ocular surgical patients [64][65][66][67][68][69][70][71][72][73][74][75], among healthcare workers [76,77] after corneal refractive surgery [77][78][79][80][81][82][83][84], in hospitalized pediatric patients [85], and in patients with chronic medical disease, immuno-suppression, or immunodeficiency [70,86].…”
Section: Target Populations and Transmissionmentioning
confidence: 99%
“…Among preterm neonates, invasive staphylococcal infections result in substantial morbidity and mortality. 1,2 Very low birth weight (VLBW) infants have an increased risk of infection due to exposure to nosocomial pathogens during extended hospitalizations. Most publications highlighting the epidemiology of infections with methicillin-resistant S aureus (MRSA) and methicillin-sensitive S aureus (MSSA) among VLBW neonates have described clusters of infections attributed to nosocomial outbreaks.…”
mentioning
confidence: 99%